Moringa oleifera seed oils: Physico-chemical characterization and its authentication using FTIR spectroscopy and chemometrics - Irnawati, Irnawati; Rohman, Abdul; Yamin, Yamin; Ahmad Fadzillah, Nurrulhidayah; Azmi, Aida Azrina; Nurlatifah, Nurlatifah; Windarsih, Anjar; Susidarti, Ratna Asmah; Ruslin, Ruslin (Elsevier, 2024)
Study on fatty acid compositions and authentication of Moringa oleifera seed oil (MOSO) is essential. MOSO from different regions had acid values of 0.32 ± 0.01 mg KOH/g, saponification values of 182.50 ± 5.95 mg KOH/g, iodine values of 78.30 ± 4.24 g I2/100 g, and peroxide values of 1.12 ± 0.02 meq O2/kg MOSO. The dominant fatty acids of MOSO were oleic acid (68.31–76.89 %) and palmitic acid (6.17–8.27 %), respectively. The che mometrics of partial least square-discriminant analysis (PLS-DA) could classify of MOSO using fatty acid com positions as variable into two distinct groups using two discriminant components in which the first and second components could describe 62.5 % and 18.7 %, respectively. Partial least square (PLS) could predict soybean oil levels as adulterant at combined wavenumbers region of 2935-2830 and 1800-710 cm− 1 . The coefficient of determination (R2 ) in calibration and validation models were of 0.9971 and 0.9961, with root mean square error of calibration (RMSEC) and root mean square error of prediction (RMSEP) of 1.67 % and 1.93 %, respectively. In summary, MOSO contains good physico-chemical properties including fatty acid compositions which are beneficial for its application in pharmaceutical, nutraceutical, and cosmetic products in the future. We concluded that the FTIR spectroscopy and chemometrics are promising tools for the authentication study and quality control of MOSO.